Increasing the number of SMEs in Kazakhstan: case of the informal sector - Nurmagambetova, Kuralay; Akhmediya, Almas; Bolatbay, Omar (Nazarbayev University Graduate School of Public Policy, 2018)
The share of SMEs in the economy of Kazakhstan is very low, despite their crucial role in generating employment and driving economic growth. The presence of a large informal sector exacerbates this situation by deterring SMEs from further development. With the Damu Fund as a client, this PAE seeks to study urban informal sector and identify key barriers for formalizing informal SMEs. Our study focuses on the city of Astana as people come here to find employment or start a business from various parts of the country and thus can be proxied as a representative of urban areas of Kazakhstan. We conducted an online survey among 60 local informal business owners who run beauty salons, manage events, provide tutoring, cleaning, etc.
Keywords: economy of Kazakhstan; small and medium enterprises; individual entrepreneur; International Finance Corporation